Comparação entre praziquantel e oxamniquine no tratamento da esquistossomose mansoni - Antônio Emanuel (Revista da Sociedade Brasileira de Medicina Tropical, 1983)
Tratamos 120 pacientes masculinos com idade de 17 a 19 anos, portadores de esquistossomose mansoni nas formas intestinal e hepatointestinal, pareados de acordo com o número de ovos por grama de fezes. Um membro de cada par tomou oxamniquine na dose de 15mg/kg e o outro, praziquantel na dose de 55mg/kg, em cápsulas. Dos 106 pacientes avaliados com pelo menos dois exames de fezes, negativaram-se 44 (83%) dos que tomaram praziquantel e 41 (77,3%) dos que tomaram oxamniquine. Ambas as drogas foram relativamente bem toleradas, com ligeira vantagem da oxamniquine. We have treated 120 patients between 17 and 19 years old with intestinal or hepatointestinal forms of Schistosoma mansoni infection. Patients were matched in pairs according to the number of eggs per gram of faeces. One member was given oxamniquine in a single dose of 15 mg/kilo/ body weight, and the other praziquantel in a dose of 55mg/kilo/ of body weight, both in capsule form. Of the 106 patients adequately evaluated (at least two stool examinations after treatment) 44 (83%) praziquantel group and 41 (77,3%) of the oxamniquine group had no eggs in the faeces. Both drugs were well tolerated but oxamniquine appeared slightly better in this regard.